Practical Ruby for System Administration - Hamou, André Ben (Apress, 2012)
It turns out that writing a book is pretty easy. Writing a book that is relevant to anyone but yourself— now that’s far more difficult than I’d imagined. I love the elegance, simplicity, and power of Ruby, and I use it every day to make systems function at the ISP where I work. You would have thought that this combination of facts would make it straightforward to distill a few salient chapters on the matter. It doesn’t. Indeed it took me nearly a month of trying to build a skeleton structure for the book before I realized that the problem was one of context.